Spheno-Orbital Meningiomas: An Analysis Based on World Health Organization Classification and Ki-67 Proliferative Index. Issue 2 (March 2018) - Belinsky, Irina; Murchison, Ann P.; Evans, James J.; Andrews, David W.; Farrell, Christopher J.; Casey, James P.; Curtis, Mark T.; Nowak Choi, Kamila A.; Werner-Wasik, Maria; Bilyk, Jurij R.
Abstract : Purpose: To evaluate the clinical behavior of spheno-orbital meningiomas with regard to World Health Organization (WHO) tumor grade and Ki-67, a cellular marker of proliferation. Methods: A retrospective review over a 16-year period of the demographic, clinical, radiographic, and surgical data of all patients with spheno-orbital meningioma who underwent surgical resection. Tumor specimens were examined histologically using the current WHO 2016 classification and immunohistochemically using Ki-67/MIB-1 monoclonal antibody. Results: Thirty-eight patients met all inclusion criteria: 78.9% of tumors were WHO grade I with a mean Ki-67 of 3.76, and 93% of patients were clinically stable at last follow up; 10.5% of lesions were WHO grade II (atypical) with a mean Ki-67 of 14.93, and 10.5% of lesions were WHO grade III (anaplastic) with a mean Ki-67 of 58.3. All grade II and III meningiomas exhibited an aggressive clinical course. There were statistically significant correlations between disease clinical progression and WHO tumor grade ( p < 0.001), between disease clinical progression and Ki-67 ( p < 0.001), and between increasing Ki-67 index and higher WHO grade ( p < 0.001). For WHO grade I lesions, a Ki-67 of ≥3.3 correlated with recurrence ( p = 0.0256). Overall, disease-specific mortality occurred in 5 (13%) patients. Conclusions: Ki-67 index is a valuable marker to use in conjunction with WHO grade to predict meningioma behavior, particularly in histologically borderline lesions, and possibly to identify a subset of WHO grade I tumors at risk of recurrence. This combination of methods can aid in tailoring treatment and surveillance strategies. Abstract : World Health Organization (WHO) grade and Ki-67/MIB-1 labeling index correlate significantly with clinical progression of spheno-orbital meningiomas.